Putative Causal Variant on Vlgr1 for the Epileptic Phenotype in the Model Wistar Audiogenic Rat - Damasceno, Samara; Fonseca, Pablo Augusto de Souza; Rosse, Izinara Cruz; Moraes, Márcio Flávio Dutra; de Oliveira, José Antônio Cortes; Garcia-Cairasco, Norberto; Brunialti Godard, Ana Lúcia (Frontiers in Neurology, 2021)
Wistar Audiogenic Rat is an epilepsy model whose animals are predisposed to develop seizures induced by acoustic stimulation. This model was developed by selective reproduction and presents a consistent genetic profile due to the several generations of inbreeding. In this study, we performed an analysis of WAR RNA-Seq data, aiming identified at genetic variants that may be involved in the epileptic phenotype. 17,085 predicted variants were identified as unique to the WAR model, of which 15,915 variants are SNPs and 1,170 INDELs. We filter the predicted variants by pre-established criteria and selected five for validation by Sanger sequencing. The genetic variant c.14198T>C in the Vlgr1 gene was confirmed in the WAR model. Vlgr1 encodes an adhesion receptor that is involved in the myelination process, in the development of stereocilia of the inner ear, and was already associated with the audiogenic seizures presented by the mice Frings. The transcriptional quantification of Vlgr1 revealed the downregulation this gene in the corpus quadrigeminum of WAR, and the protein modeling predicted that the mutated residue alters the structure of a domain of the VLGR1 receptor. We believe that Vlgr1 gene may be related to the predisposition of WAR to seizures and suggest the mutation Vlgr1/Q4695R as putative causal variant, and the first molecular marker of the WAR strain.